Effective Leadership Transition and Successful Succession in the Family Business Dines, d.o.o. - Civić, Aila; Marič, Miha (Izzivi prenosa vodenja na naslednjo generacijo v družinskem podjetju, 2025)
Successful succession implementation is crucial for business continuity, as failure can seriously threaten a company’s existence. The succession process includes the transfer of leadership or ownership, which is especially significant for family businesses such as Dines d.o.o., engaged in importing, servicing, and installing heat pumps, air conditioning, and ventilation systems. The study first examined concepts of effective leadership, modern leadership traits, and family entrepreneurship. Based on these insights, a structured interview with Domn Deu was prepared, covering three areas: effective leadership and the leader, succession in family business, and factors influencing ownership transfer. Analysis of the responses revealed key challenges and opportunities in succession and highlighted the importance of innovative approaches for a successful business transfer. Based on the findings, a 3K succession model for small and medium-sized enterprises was developed.